Service Quality impact in Higher Education Institutions of Aizawl (International Journal of Food and Nutritional Sciences, 2022)
In the modern world, education plays an important role in the aspects of human life as well as society. The growth and development of mankind are being brought about by education. For this, educational institutions are the most important tools which provide formal education. Since quality can be considered the heart of education, providing quality education is an important factor in transforming and developing society as well as human beings. The main objective of this study is to determine the impact of service quality in Higher Education Institutes in Aizawl. Two Government colleges with the highest enrollment were selected for the study. The SERVQUAL model comprising five dimensions such as tangible, reliability, responsiveness, assurance, and empathy was used to frame the questionnaire to obtain the gaps between perception and expectation.